Semi-nested Taqman real-time quantitative PCR for noninvasive prenatal diagnosis of Bart's hydrops fetalis - Sakorn Pornprasert (2018)
Background: Non-invasive prenatal diagnosis based on detection of fetal cell-free DNA is limited when mother and father are both carriers for the same autosomal recessive mutation. Objective: Develop the semi-nested Taqman real-time PCR for quantification of α-thalassemia-1 SEA type deletion allele in plasma of α-thalassemia-1 SEA carriage pregnancies. Material and Method: Plasma DNA was extracted from six women who carried fetuses with normal, 11 with heterozygote α-thalassemia-1 SEA type deletion and seven with Bart's hydrops fetalis. DNA was amplified using conventional PCR with the primary specific primer set for α-thalassemia-1 SEA type deletion. PCR product was then subjected to the semi-nested realtime PCR using the secondary specific primer and Taqman probe set for α-thalassemia-1 SEA type deletion. The standard curve was constructed using ten-fold serial dilutions of conventional PCR product of the heterozygote α-thalassemia-1 SEA type deletion. Results: Women who carried fetuses with Bart's hydrops fetalis displayed a trend toward higher mean copy number of α-thalassemia-1 SEA type deletion allele vs. women who carried fetuses with normal and heterozygote, albeit not reaching statistical significance. Conclusion: The maternally inherited fetal allele present in maternal plasma is difficult to discern the fetal cell-free DNA from a higher background DNA of the mother. Thus, further investigation is needed to improve the diagnosis of Bart's hydrops fetalis using this technique.